(untitled) (REMUNOM, 2025)
ABSTRACT This article examines the relationship between education and human rights, focusing on the analysis of public policies aimed at youth and guaranteeing the rights of apprentices in Brazil. The study addresses the impact of government initiatives in combating social exclusion and promoting the educational and professional inclusion of young people. Based on a literature review, it discusses how the Youth Statute and the Apprenticeship Law have contributed to citizenship formation and access to the job market. Despite the advances, it identifies the need for greater coordination between the public and private sectors to enforce these rights and overcome challenges such as precarious working conditions and unequal access to quality education. It is concluded that promoting education integrated with human rights is essential to guarantee the full development of young people. KEYWORDS: Education. Human rights. Youth KEYWORDS: Education. Human rights. Youth